(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1973)
An analysis of the structural features and artefacts associated with the recumbent stone circles (RSCs) of NE Scotland (74 certain and 18 probable examples). An origin in the Clava-cairn tradition of Inverness-shire is most likely, with the main activity between 1800 and 1400 BC. Analysis of the occurrence of nine early and eight late features indicates a primary area of RSC development around Insch (Aberdeenshire), from which the small stone circles and four-posters of Perthshire were later derived. The azimuths of RSCs show a consistent but astronomically meaningless pattern of solar orientation, and despite the frequency of associated burials a primarily sepulchral function cannot be proved. A R